Investing in a More Sustainable Indonesia : Country Environmental Analysis 2009 - Main Report - World Bank (World Bank, 2012)
The objective of this Country Environmental Analysis (CEA) is to highlight the underlying challenges and opportunities for Indonesia's environment and management of its natural resources in order to guide the World Bank support to Indonesian institutions for more sustainable development. Rather, the CEA sets the broader context (chapter one) and economic costs of environmental degradation (chapter two) in order to identify underlying challenges and opportunities. These are divided into two sets of priorities those related to environmental governance and those that are more sectoral in nature. Environmental governance encompasses the decentralized framework for environmental management (chapter three), enabling policies for greater environment and resource sustainability (chapter four) and building environmental constituencies (chapter five). The sectoral challenges that are most important for Indonesian development are vulnerability to climate change (chapter six), land use and climate change (chapter seven) and energy and climate change (chapter eight). The report concludes with options for a more sustainable Indonesia, including recommendations for how the World Bank can more effectively invest in light of the CEA findings (chapter nine).